2011
DOI: 10.1210/jc.2010-1624
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Pregnant Patient with Thyroid Cancer

Abstract: Thyroid cancer, the most common endocrine malignancy, increased progressively from 1972 through 2002 largely as the result of an increasing incidence of small papillary thyroid cancers, the majority of which are less than 2 cm and which increased almost 3-fold during the 30-yr study. During this time, thyroid cancer was found to affect women more often than men by a ratio of almost 3 to 1. Moreover, papillary thyroid cancer was found to be the most common form of differentiated thyroid cancer among women of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Most recurrences of DTC occur within the first five years after initial treatment, but recurrences may occur many years or even decades later, particularly in patients with papillary cancer [16, 17]. In addition to this, decisions about cancer treatment during pregnancy are associated with ethical conflicts between the best option for the mother and for the fetus [18, 19]. The management of pregnant women with cancer should consider the maternal-fetal risk related to treatment, as well as the possibility of tumor progression for postponing treatment or for the tumor being related to pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Most recurrences of DTC occur within the first five years after initial treatment, but recurrences may occur many years or even decades later, particularly in patients with papillary cancer [16, 17]. In addition to this, decisions about cancer treatment during pregnancy are associated with ethical conflicts between the best option for the mother and for the fetus [18, 19]. The management of pregnant women with cancer should consider the maternal-fetal risk related to treatment, as well as the possibility of tumor progression for postponing treatment or for the tumor being related to pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated the potential for progression of thyroid cancer during and after pregnancy, highlighting the thyroid-stimulating effects of human chorionic PREGNANCY AND THYROID CANCER 69 gonadotropin (hCG) and increased levels of estrogen during pregnancy as possible mechanisms (10). In a recent metaanalysis, Zhou et al reported that the odds ratio of developing thyroid carcinoma among women with a history of pregnancy was similar to non-pregnant controls.…”
Section: Discussionmentioning
confidence: 99%
“… 86 Additional indications to consider surgery during pregnancy may include rapid growth rate, nodal metastasis or features such as extracapsular invasion. 87 …”
Section: Thyroid Nodules and Cancermentioning
confidence: 99%